Measuring Amil Happiness Using Psychological Approach: Evidence from Yogyakarta, Indonesia - Zaki Abdullah; Dinda Aisyah Najmi; Duddy Roesmara Donna (International Journal of Zakat, 2019)
The implementation of Good Amil Governance as one of the important aspects of a standard of international zakat management, which is stated in Zakat Core Principles, requires an approach that is more than just amil competence and qualification aspects. The psychological perspective of amil also needs to be considered to obtain and maintain the best human resources. As a profession that is oriented towards social benefits, an amil has different working rhythm and consequences. This research aims to measure level of amil’s happiness in the workplace and further study its impact on amil productivity. The result shows that amil is a satisfying job. Further, the most blissful factor for amil is work motivation, while the most unhappy factor for amil is the career path, which seems to be less promising. In addition, the happiness level of amil has a positive relationship with his or her productivity level. Therefore, psychology condition of an amil should be considered in order to increase the performance of zakat institutions.